When the mountains change their tune - Stodart, Eleanor (North Ryde, NSW : Methuen Australia, 1985)
While skiing in the Snowy Mountains of Australia, four teenagers become lost in a blizzard.
Keywords: Survival -- Fiction; Skis and skiing -- Fiction; Blizzards -- Fiction; Australia -- Fiction